2021
DOI: 10.1108/jed-02-2021-0025
|View full text |Cite
|
Sign up to set email alerts
|

Sub-national union coverage and the youth's labor market outcomes: evidence from a national survey in Vietnam

Abstract: PurposeThis paper examines the effects of sub-national union coverage on the youth's labor market outcomes.Design/methodology/approachIn the context of the private business sector in Vietnam, this study link individual labor market data with union coverage at provincial level in the period 2013–2016 to investigate the effects of sub-national union coverage on the youth's labor market outcomes. Contingent on the outcome variable, we use the OLS and probit model that control for diverse individual characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…More importantly, Heterotrait-Monotrait analysis was used as an additional examination to affirm the discriminant validity of the constructs. The HTML values ranged from 0.185 to 0.826 (Table 4), which were less than 0.9 (Pérez-Fernández et al , 2022; Bach et al , 2021). Thus, the reliability and discriminant validity of the constructs were verified (Hair et al , 2021; Podsakoff et al , 2003).…”
Section: Methodsmentioning
confidence: 99%
“…More importantly, Heterotrait-Monotrait analysis was used as an additional examination to affirm the discriminant validity of the constructs. The HTML values ranged from 0.185 to 0.826 (Table 4), which were less than 0.9 (Pérez-Fernández et al , 2022; Bach et al , 2021). Thus, the reliability and discriminant validity of the constructs were verified (Hair et al , 2021; Podsakoff et al , 2003).…”
Section: Methodsmentioning
confidence: 99%
“…Each generation group will have significant differences and differences in thinking and lifestyle (Nguyen et al, 2019). Presently, in the 20s of the 21st century, it is been accepting young citizens of Gen Z. Nguyen (2020), Bach et al (2022) showed that generation is a diverse, hyper-connected, short-lived group of influencers who are the business force across industries, brands, and digital platforms. Generation Z is the number one generation to write positive things online, showcase brands, and more.…”
Section: Mobile Banking Trendmentioning
confidence: 99%
“…The labor market has considerably altered in recent decades, and the work environment has been fundamentally transformed by the diversity of the workforce, technological and social changes, and the increase in globalization, resulting in crucial changes in how people enact their career choices [ [1] , [2] , [3] , [4] , [5] ]. As such, entrepreneurship has become a popular career choice among youths while new venture creation is often identified as the most important outcome and the heart of the entrepreneurial process [ [6] , [7] , [8] ].…”
Section: Introductionmentioning
confidence: 99%